Well-being of students in higher education: The importance of a student perspective - Douwes, Rynke; Metselaar, Janneke; Pijnenborg, Gerdina Hendrika Maria; Boonstra, Nynke (Cogent education, 2023)
Recently, there has been an increased interest in the well-being of students in higher education. Despite the widespread consensus on the importance of student well-being, a clear definition continues to be lacking. This study qualitatively examined the student perspective on the topic through semi-structured interviews at a university of applied sciences in the Netherlands (n = 27). A major recurring theme was well-being as a balance in the interplay between efforts directed towards studies and life beyond studies. This method of perceiving well-being deviates from theoretical definitions. Students mentioned various factors that influence their well-being. Responses ranged from personal and university related factors to external factors beyond their educational institution. This study contributes to the body of knowledge on the well-being of students in higher education and provides suggestions for educational institutions, such as incorporating a holistic perspective on students and learning; and focus points for the development of policies and practices.